Estudo da patogenicidade e controle biológico de fusarium sp. com trichoderma sp. - Pereira, Carolina de Oliveira Fialho (My University, 2014)
Phytopathogenic fungi belonging to Fusarium genera are known as the agents responsible of many diseases in plants. Among these, tomato plants are attacked by the 3 races of Fusarium oxysporum f. sp. lycopersici (Fol), which causes vascular wilt. To control this disease, many techniques have been employed, mostly the use of resistant cultivars and chemical fungicides. Alternatively, the use of antagonistic microorganisms for biological control and decrease of inoculum of plant pathogens by introducing mass production of Trichoderma sp. has been studied for many years. In this study we evaluated the pathogenicity of 10 isolates of Fol on differential cultivars of tomato, where only four of ten isolates proved pathogenic to susceptible cultivar to this disease and none of which was diagnosed as belonging to race 3. The results obtained in tests of direct confrontation with Trichoderma sp. isolates showed high variability in relation to mycoparasitism, with the best results for agressiveness the isolates T3, T8 and T17. In these cases it was observed evidence of growth of the host colony for at least six of nine isolates tested. Regarding the inhibitory effect of these isolates, the results of greater inhibition of colony growth of plant pathogenic fungus were obtained for the isolated T3 and T2. The strain 34970 of Fol was the least inhibited by isolates of Trichoderma sp., and isolated TO 11 showed the highest average of inhibition. With regards to the production of volatile metabolites, only the isolates Fusarium 23, Fusarium 27 and 34970 of Fol were inhibited after 120 hours of testing. In the biological control of Fusarium wilt of tomato caused by isolate TO 245, seedlings treated with isolates T6 and T17 of Trichoderma sp. showed a lower incidence of disease, with 1.25 and 0.75 respectively compared to 1.87 of the control group in accordance with scale of severity of disease by Vakalounakis et al. (2004). The treatments with the isolates T6 and T17 in substrate inoculated with isolate 1205/2 showed values of 0.5 and 0.375 according to the scale, compared with 0.5 in the control treatment without the presence of Trichoderma sp. The average height, length and dry weight of roots did not differ significantly for any treatment. The dry weight of shoot was significantly higher for plants treated with isolate T6 in substrate infested by the isolated 1205/2. All the pathogenic isolates of Fol were paired with the standard strains of vegetative compatibility groups and showed signs of heterokaryosis with the standard strain 34970 corresponding to VCG 0030, indicating a possible genetic similarity among the isolates used.
Os fungos fitopatogênicos pertencentes ao gênero Fusarium são conhecidos causadores de doenças de plantas em diversos hospedeiros. Dentre os quais se destaca o tomateiro, atacado pelas três raças conhecidas de Fusarium oxysporum f. sp. lycopersici (Fol), causadoras da murcha vascular. Para o controle dessa doença, o emprego de microrganismos, como os isolados antagonistas de Trichoderma sp. pode ser uma alternativa ao emprego de agroquímicos. No presente trabalho foi avaliada a patogenicidade de dez isolados de Fol em cultivares diferenciadoras de tomateiro, sendo que apenas quatro se mostraram patogênicos a cultivar suscetível, e nenhum deles foi diagnosticado como pertencente à raça 3. Os resultados obtidos nos testes de confronto direto com os isolados de Trichoderma sp. apresentaram alta variabilidade em relação à capacidade micoparasítica, com os melhores resultados de sobreposição para os isolados T3, T8 e T17. Nestes casos foi observada evidência de sobreposição da colônia do hospedeiro para pelo menos seis dos nove isolados antagonistas. Em relação à capacidade inibitória destes isolados, os resultados de maior inibição de crescimento da colônia do fitopatógeno foram obtidos para os isolados T2 e T3. A linhagem 34970 de Fol foi a mais resistente às ações antagonistas dos isolados de Trichoderma sp., e o isolado TO 11 sofreu as maiores médias de inibição. Em teste de produção de metabólitos voláteis somente os isolados Fusarium 23, Fusarium 27 e 34970 de Fol, foram inibidos após 120 horas de teste. No controle biológico da fusariose do tomateiro, provocada pelo isolado TO 245 de Fol, as plântulas tratadas com os isolados T6 e T17 de Trichoderma sp. apresentaram menor incidência de doença, com notas iguais a 1,25 e 0,75 respectivamente em comparação a 1,87 do grupo controle, de acordo com a escala de severidade de doença de Vakalounakis et al. (2004). Os tratamentos com os isolados T6 e T17 em substrato contaminado com o isolado 1205/2 de Fol apresentaram valor de 0,50 e 0,38, de acordo com a escala, em comparação com 0,50 do tratamento controle. As médias de alturas, comprimento e peso seco das raízes não apresentaram diferença estatística para nenhum dos tratamentos, porém o peso seco da parte aérea foi significativamente maior para as plantas tratadas com o isolado T6 em substrato infestado pelo isolado 1205/2 de Fol. Todos os isolados patogênicos pareados com as linhagens padrão dos grupos de compatibilidade vegetativa apresentaram sinais de heterocariose com a linhagem padrão 34970 correspondente ao GCV 0030, indicando uma possível similaridade genética entre os isolados utilizados.
Keywords: Fusarium; Fungos; Controle biológico